Глущенко В. А., Ледняк Ю. В., Овчаренко В. М., Рябініна І. М. Мова як система - Іванова, Л. (Мовознавство, 2011)
Рецензія на книгу: Глущенко В. А., Ледняк Ю. В., Овчаренко В. М., Рябініна І. М. Мова як система. К. :Б. в., 2011, — 132 с.